Edutainment of Soft Skills Materials in Non-Classroom Learning to Improve Achievement and Independence in Vocational Schools - Mustafa Kamal; Muhajir Muhajir; Nuril Huda (International Journal of Studies in International Education, 2025)
This study aims to explore the application of the Edutainment method in learning soft skills through non-classroom activities in vocational schools, and its impact on student achievement and independence. In an era of increasingly competitive globalization, soft skills such as communication, teamwork, leadership, and self-management are the keys to success in the world of work. By combining educational and entertainment aspects, the Edutainment method is expected to be able to increase student learning motivation and engagement. This study uses a qualitative approach with a descriptive method to analyze data obtained from interviews, observations, and documentation at SMKN 1 Gunung Kijang. The results show that this method is effective in developing students' soft skills, despite obstacles in its implementation, such as limited resources and infrastructure. The proposed solution includes increasing teacher training and parental involvement in supporting soft skills-based extracurricular activities. Overall, the Edutainment method has been proven to be able to increase students' independence and achievement, while also preparing them to compete in the world of work.